Comparison of Bond Strength in the Different Class of Resin Cements to Cast and CAD/CAM Co-Cr Alloys - Leyla Sadighpour; Azam S. Mostafavi; Maryam Pirmoradian; Fatemeh Alipuryalda (Hindawi Limited, 2021)
Objectives. Despite the widespread use of resin cements in cementing dental restorations, their bond strength to CAD/CAM base metal alloys is not widely studied. This study aimed to evaluate the microshear bond strength (μSBS) between cobalt-chrome (Co-Cr) alloys fabricated using casting or CAD/CAM methods with three types of resin cements. Materials and Methods. Fifty Co-Cr blocks were prepared with CAD/CAM or casting technique. Specimens were divided using primer or not and bonded to three types of resin cements: Panavia F2, RelyX Unicem, and Duo-Link. The differences between the mean μSBS values were analyzed using the two-way ANOVA test and Tukey analysis (α = 0.05). The mode of failure was evaluated using a stereomicroscope. In addition, the specimens were examined by scanning electron microscopy (SEM) based on two received signals: backscattered electrons (SEB) and secondary electrons (SEs). One intact alloy specimen in each group was analyzed by energy-dispersive X-ray spectroscopy (EDX). Results. Most of the specimens in the no-primer group were prematurely debonded. Statistical analyses showed that the interaction between the alloy substrate and cement type was significant (p=0.001). The bond strength of Panavia F2 was significantly higher than Duo-Link in the CAD/CAM group (p=0.001). SEM evaluation confirmed the difference in grain structures, while EDX showed no remarkable difference in the chemical composition of the alloy substrates. Conclusion. Alloy fabrication technique may influence the bond strength of resin cements. In the CAD/CAM group, cement containing MDP molecules exhibited higher strength than the etch-and-rinse one.